Penerapan QR Code Untuk Media Pelayanan Absensi Mahasiswa AMIK Dian Cipta Cendikia - Didi Susianto; Reni Astika; Yuli Syafitri (Jurnal ICT : Information Communication & Technology, 2021)
Attendance is something that must be done by students. In the attendance process, the AMIK Dian Cipta Cendikia College still uses the manual method. Therefore, we need a student attendance system that can collect data and manage data so that it can be done quickly, efficiently and accurately. One of technology developed is QR Code. QR Code is an essential thing because of its ability to store larger data so that it can provide fast and accurate services. One of the things that can be done to support the author in designing an Application of QR Code for Attendance Service Media for student in AMIK Dian Cipta Cendikia is by using the Extreme Programming research method. The purpose of this application is expected to make the attendance process will be more efficient and can be easily monitored by lecturers and by the academic department. The results of this research were in the form of a student attendance application that uses a QR code. It is used as the input media for student attendance based on a local network implemented in order to create an attendance information system that provides convenience for students in the attendance process, reduces fraud committed by students, and facilitates reports when conducting recapitulation.